Enhancing the Implementation of Shariah Review Practices in Islamic Banks - MUHAMMAD NAJIB MOHD AMIN,; NOR HAFIZAH ZAINAL ABIDIN,; NORI YANI ABU TALIB, (Asian Journal of Accounting Perspectives, 2024)
Research aim: BThe aim of the present study is to understand how Shariah review practices are being implemented by gathering the perceptions of Shariah officers at different Islamic banks (IBs). This is done through analysis of similarities and differences of Shariah review practices across different IBs. Design/ Methodology/ Approach: Data was gathered through semi-structured interviews with six Shariah officers, including managers and executive levels from five different IBs. Research finding: Utilising an institutional perspective, the findings suggest that coercive isomorphism through comprehensive guidelines on Shariah review practices promote consistent implementation of Shariah review procedures. In addition, the findings reveal that systematic communications of issues in Shariah review findings to the management and reporting the final findings to a Shariah committee is crucial in minimising threats of independence. Finally, timeliness in reporting and leveraging on other functions is proposed to enhance the effectiveness of Shariah review practices. Theoretical contribution/Originality: This study applies institutional theory in assessing of how Shariah review practices are being implemented in Malaysian IBs. Comparatively, most prior studies utilise agency theory, which considers Shariah review practices as an oversight function in IBs. Practitioner/Policy implication: Insights from this study underline the importance of comprehensive guidelines on Shariah review practices. This is because they enhance the standardisation of practices which improves the comparability, understandability, and quality of the work performed by Shariah officers. The study also suggests that IBs revisit their leveraging models to ensure efficient coordination of resources and improve reporting to their Shariah committees. Originality/value: This study contributes to the literature on the establishment of the Shariah review function and internal modules of Shariah review practices through normative, coercive, and mimetic isomorphisms.